2020
DOI: 10.5551/jat.49619
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fetuin-B with Subclinical Atherosclerosis in Obese Chinese Adults

Abstract: We aimed to explore the independent associations of serum Fetuin-B and common genetic variants in FETUB locus with subclinical atherosclerosis. Methods: A cross-sectional study of 1,140 obese adults, who underwent serum Fetuin-B testing, hepatic ultrasonography scanning, genotyping on four tagging single nucleotide polymorphisms (SNPs) in FETUB locus and atherosclerosis detection, was conducted in Xiamen, China. Results: Increasing tertiles of brachial ankle pulse wave velocity (ba-PWV) were significantly asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…FBLN1 is abundant in the plasma and arterial walls of patients with type 2 diabetes and can be used as a predictor of cardiovascular mortality in patients with type 2 diabetes [41]. An independent risk factor for type 2 diabetes is the plasma levels of AHSG, which is an insulin receptor inhibitor secreted by the liver and, along with FETUB [42,43], thought to be an important factor in insulin resistance in obesity [44,45]. GPLD1 serves as a biomarker that effectively differentiates latent autoimmune diabetes in adults from type 2 diabetes in the early stage [46], and it was shown that the circulating GPLD1 concentration in diabetic rats could be restored to normal levels by exercise training [47].…”
Section: Discussionmentioning
confidence: 99%
“…FBLN1 is abundant in the plasma and arterial walls of patients with type 2 diabetes and can be used as a predictor of cardiovascular mortality in patients with type 2 diabetes [41]. An independent risk factor for type 2 diabetes is the plasma levels of AHSG, which is an insulin receptor inhibitor secreted by the liver and, along with FETUB [42,43], thought to be an important factor in insulin resistance in obesity [44,45]. GPLD1 serves as a biomarker that effectively differentiates latent autoimmune diabetes in adults from type 2 diabetes in the early stage [46], and it was shown that the circulating GPLD1 concentration in diabetic rats could be restored to normal levels by exercise training [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that CIMT was increased in PCOS subjects compared to controls. Growing evidence suggest that there is a link between fetuin-B and cardiovascular disorders [9,24]. Moreover, fetuin-B increases inflammation in vascular plaque and also causes vascular plaque vulnerable [10].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with OSA, the risk of hypertension [ 2 ], treatment resistance [ 3 ], ischemic heart disease [ 4 ], cardiovascular events, arrhythmias, heart failure [ 2 ], stroke [ 5 ], neurodegenerative diseases, and poor cognitive performance [ 6 ] is increased. One of the agents known to be involved in atherogenesis is Fetuin-A (Fet-A) [ 7 , 8 ]. Produced in the liver, Fet-A is a glycoprotein that limits the calcification of the vessels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%